Protein Engineering Technology and Application - Ogawa, Tomohisa (IntechOpen, 2013)
Given the centrality of protein to many biological process, this book makes a significant contribution to the fields of healthcare and nutrition. Its chapters consider topics such as protein-protein and protein-ligand docking, and the protein engineering of enzymes involved in bioplastic metabolism. One contribution gives an overview of the In Vitro Virus (IVV) analytic method, while another shows how cutting-edge techniques in protein engineering advance our knowledge in the field of palaeontology. The book also includes a review of classic and alternative strategies when using yeasts in research, with a focus on Pichia pastoris as a host. Finally, there are two contributions on chromatography: one on the method itself, and another on its use to identify HMGB1-binding components.